Development of chipless and wireless underground temperature sensor system based on magnetic antennas and SAW sensor - Kim, Sihyeok; Adib, Md Ridwan; Lee, Keekeun (Sensors and Actuators, A: Physical, 2019)
A chipless and wireless underground sensor system was developed based on two magnetic coil antennas with magnetic cores and a surface acoustic wave (SAW) resonator sensor to monitor temperature variations around buried utilities from the ground. A ∼250 MHz alternating current from the magnetic antenna generates a SAW along the piezoelectric substrate, and the returned SAW energy owing to the reflection bars on the sensor is reconverted to magnetic flux by the sensor's interdigital transducer (IDT) and subsequently transmitted to a reader via magnetic antenna. By observing changes in the center frequency of the SAW sensor with temperature, we were able to monitor the underground temperature variations in real time. The developed magnetic coil antenna has a large diameter Ni0.8Fe0.2 core wound by Cu coil, and a convex shape at the core end to converge the magnetic flux and enhance the readout distance. Two types of temperature sensors, a one-port SAW resonator and two-port SAW reflective delay line, were fabricated on a 128° YX LiNbO3 and their characteristics were compared in terms of soil temperature. SAW generation by magnetic antenna followed by SAW propagation along the piezoelectric substrate were each confirmed by the AC voltages derived at the output IDT on the SAW sensor, and the amplitude of the SAW was greatly dependent on the current applied to the coil. In soil testing, long readout distance between the reader and underground SAW sensor was observed. The temperature sensors provided stable performance in terms of underground temperature changes, soil type, and soil compactness at that readout distance. The resultant sensitivity and linearity for the SAW resonator temperature sensor was 0.3 MHz/ºC and 0.96, respectively. COMSOL and coupling of Mode (COM) modeling were also performed to find the optimal sensor system parameters and predict the results in advance.
Keywords: Interdigital transducer; Magnetic coil; NiFe core; Piezoelectric substrates; Reflective delay line; SAW resonators; Surface acoustic wave resonators; Underground temperature; Magnetic coil antenna; NiFe core; SAW reflective delay line; SAW resonator; Wireless underground sensor